1998
DOI: 10.1021/bi9800449
|View full text |Cite
|
Sign up to set email alerts
|

Ca2+ Coordination to Backbone Carbonyl Oxygen Atoms in Calmodulin and Other EF-Hand Proteins:  15N Chemical Shifts as Probes for Monitoring Individual-Site Ca2+ Coordination

Abstract: Examination of the NMR 15N chemical shifts of a number of EF-hand proteins shows that the shift value for the amido nitrogen of the residue in position 8 of a canonical EF-hand loop (or position 10 of a pseudo EF-hand loop) provides a good indication of metal occupation of that site. The NH of the residue in position 8 is covalently bonded to the carbonyl of residue 7, the only backbone carbonyl that coordinates to the metal ion in a canonical EF-hand loop. Upon metal coordination to this carbonyl, there is an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
104
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 98 publications
(116 citation statements)
references
References 85 publications
12
104
0
Order By: Relevance
“…3A) show an increase in pK a for peptide His19 from 6.35 (free) to 7.25 (complex), indicating that the protonated form is stabilized in the complex with Ca 4 CaM. In contrast, the pK a for His107 in Ca 4 CaM decreases by a smaller amount from 6.15 to 5.85 on complex formation with the peptide.…”
Section: Determination Of Histidine Pk a Valuesmentioning
confidence: 93%
See 3 more Smart Citations
“…3A) show an increase in pK a for peptide His19 from 6.35 (free) to 7.25 (complex), indicating that the protonated form is stabilized in the complex with Ca 4 CaM. In contrast, the pK a for His107 in Ca 4 CaM decreases by a smaller amount from 6.15 to 5.85 on complex formation with the peptide.…”
Section: Determination Of Histidine Pk a Valuesmentioning
confidence: 93%
“…Initial studies with the P 9-26 peptide showed that the strength of the interaction with Ca 4 CaM is strongly pH-dependent, with K d varying from 0.8 to 300 nM for pH 5.0-8.5 (Skinner, PhD thesis, University of London, 1996). For quantitation of the high affinity 1:1 complex formed with peptide P 1-21 at lower pH values, competition titrations were performed, using spectroscopically ''silent'' peptides (FFFu, K d ¼ 750 ± 120 pM and FFFp, K d ¼ 45 AE 5pM [2]), whose affinity was established to be pH-independent in titrations of the Ca 4 CaMWFFu complex as a function of pH (Fig.…”
Section: Peptide Binding Affinity As a Function Of Phmentioning
confidence: 99%
See 2 more Smart Citations
“…7-10). In NMR spectroscopy, metal coordination to a backbone carbonyl can cause deshielding of the backbone nitrogen atom of the succeeding residue (31 We constructed plasmids carrying ccbP genes encoding the wild type protein or mutants at site I under the control of the petE promoter (32). The plasmids were used to transform Anabaena sp., so that the expression of ccbP was inducible with copper.…”
Section: Nmr Structure Of Ca 2ϩmentioning
confidence: 99%